2020
DOI: 10.1111/1467-9817.12293
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent word reading in English as a foreign language

Abstract: The current study examined the proficiency of Israeli adolescents in reading single words in English, which is taught as a foreign language, and what language skills predict individual variability. Parallel measures of word reading, phonology, decoding, morpho-syntax and vocabulary in Hebrew and English were administered to 217 adolescents in 8th and 11th grade. Following 5-8 years of English as a foreign language instruction, participants achieved reading levels commensurate with those of third to fourth grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…The results of the current study demonstrated less efficient reading in L2 than in L1 for intermediate proficiency bilinguals—both in bottom-up processing (lexical access) and in top-down processing (the ability to generate expectation). Importantly, this was the case even though the participants we tested had been studying their L2 for more than 10 years and were exposed to it on a daily basis, especially in the written form (see also Prior et al, 2020). This pattern suggests that the magnitude of word frequency effects is a marker of reading efficiency, associated with language use and proficiency (Brysbaert et al, 2017; Diependaele et al, 2013; Gollan et al, 2011) and that the magnitude of word predictability effects might be a marker of higher order reading efficiency, indexing compensatory processing (Stanovich, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the current study demonstrated less efficient reading in L2 than in L1 for intermediate proficiency bilinguals—both in bottom-up processing (lexical access) and in top-down processing (the ability to generate expectation). Importantly, this was the case even though the participants we tested had been studying their L2 for more than 10 years and were exposed to it on a daily basis, especially in the written form (see also Prior et al, 2020). This pattern suggests that the magnitude of word frequency effects is a marker of reading efficiency, associated with language use and proficiency (Brysbaert et al, 2017; Diependaele et al, 2013; Gollan et al, 2011) and that the magnitude of word predictability effects might be a marker of higher order reading efficiency, indexing compensatory processing (Stanovich, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the current results, which highlight the distinction between efficient reading in the L1 and L2, have important implications. On the downside, even readers who have achieved a high level of skill in the L1 are not guaranteed to reach equivalent levels of skill when studying a second language, especially if the L2 is very different from the L1 (Prior et al, 2020). On a more encouraging note, however, the current results suggest that to achieve efficient reading in an L2, individuals should strive to broaden their vocabulary knowledge and the rapid accessibility of mappings from form to meaning in that language.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the traditional teaching mode, the classroom is "teacher-centered", with teachers instilling one-way instruction on the podium and students passively accepting it at their desks, which gives people the impression that education is all about indoctrination. Under the blended teaching mode, teachers and students teach in information interaction, which makes people realize that learning is a kind of knowledge transmission rather than the process of knowledge instillation [10][11].…”
Section: Introductionmentioning
confidence: 99%